2021
DOI: 10.1021/acssensors.1c00462
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Boronic Acid-Based Saccharide Sensors

Abstract: Boronic acids can reversibly bind diols, a molecular feature that is ubiquitous within saccharides, leading to their use in the design and implementation of sensors for numerous saccharide species. There is a growing understanding of the importance of saccharides in many biological processes and systems; while saccharide or carbohydrate sensing in medicine is most often associated with detection of glucose in diabetes patients, saccharides have proven to be relevant in a range of disease states. Herein the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 153 publications
2
76
0
Order By: Relevance
“…The fact that changing the hybridization of boron-containing moieties from tetrahedral to trigonal planar induces such marked fluorescence decreases has been previously reported in the literature (Samaniego Lopez et al, 2015;Williams et al, 2021), and is fully consistent with the results reported herein. Notably, this fluorescence quenching occurs rapidly (within seconds), and remains stable (with less than 5% additional quenching) up to 20 min after the initial contact between compound 1 and water.…”
Section: Resultssupporting
confidence: 93%
“…The fact that changing the hybridization of boron-containing moieties from tetrahedral to trigonal planar induces such marked fluorescence decreases has been previously reported in the literature (Samaniego Lopez et al, 2015;Williams et al, 2021), and is fully consistent with the results reported herein. Notably, this fluorescence quenching occurs rapidly (within seconds), and remains stable (with less than 5% additional quenching) up to 20 min after the initial contact between compound 1 and water.…”
Section: Resultssupporting
confidence: 93%
“…The observation demonstrates higher affinity binding through synergistic recognition by boronic acid installed WGA peptide, which is difficult to achieve either by WGA peptide or individual boronic acid probe. P4 showed the highest affinity in the panel of borono-WGA peptides due to a better association ability of BA4 with sialic acid (Wulff-type boronate) 42,66 and feasibly an additional H-bonding between acetamide of sialic acid and water inserted structure of BA4 (ESI Fig. S53), which we plan investigating in future.…”
Section: Resultsmentioning
confidence: 99%
“…The given significance of sialyl-glycan in pathophysiology warrants extensive research on designing inexpensive probes for potent sensing of sialyl-antigens. In this regard, BA-based small molecules named 'boronolectins' have shown a fantastic benefit 10,[38][39][40][41][42][43] . Although, we and others 36,[44][45][46][47][48] reason, developing peptide boronolectins probe may advance selectivity, biocompatibility and sensing capability of specific glycan.…”
Section: Introductionmentioning
confidence: 99%
“…1 They hold great potential in many applications including sensing, bioimaging, information encoding, and soft robotics. [2][3][4][5][6] Researchers are focusing on preparing FHs with stimuli responsiveness and self-healing ability to extent their application into broader fields. Functional FHs such as stimuli responsiveness, self-healing ability and shape-memory are commonly derived from special cross-linking between polymer chains.…”
Section: Introductionmentioning
confidence: 99%